Auxis rochei ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Auxis rochei (Risso, 1810). Bullet Tuna. To 55 cm (21.6 in) TL (Nakamura in Masuda et al. 1984). Circumglobal; western Pacific Ocean north to southern Kuril Islands (Parin 2003); between Halfmoon Bay and San Francisco, central California (Personal communication: California Academy of Sciences Fish Collection, San Francisco, California) to northern Chile (Pequeño 1997), including Gulf of California (Collette in Fischer et al. 1995), and Islas Galápagos (Grove and Lavenberg 1997). Neritic and oceanic epipelagic; depth: surface to 200 m (656 ft) (Robertson and Allen 2002). The eastern Pacific form is recognized as the subspecies Auxis rochei eudorax Collette and Aadland 1996 (Collette 2003). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 211, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...